Hubungan Persepsi Mutu Pelayanan dengan Minat Kunjungan Ulang Pasien di Klinik Wahyu Medika : The Relationship Between Perceptions of Service Quality and Patient's Re-Visit Interest at The Wahyu Medika Clinic - Mandala Putri, Heryn; Luvi Dian Afriyani (Indonesian Journal of Midwifery (IJM), 2025)
The quality of health services is a health service that can satisfy every user of health services in accordance with the level of community satisfaction. Good service can increase patient interest in making repeat visits. Based on the results of a preliminary study conducted at the Wahyu Medika Clinic, data on the number of patient visits in the period January-August 2024 was obtained as many as 8,254 people. The target number of patient visits was formulated in early 2024, namely 1200/month with an average of 40 patients per day, this shows that patient visits did not meet the target. The patient satisfaction survey score conducted by the Wahyu Medika Clinic was obtained 60% stated that they were satisfied and 40% stated that they were less satisfied. This study aims to determine the relationship between perceptions of service quality and patient interest in repeat visits at the Wahyu Medika Clinic. This type of research uses a quantitative method through a correlational analytical design with a cross-sectional approach. The population in this study were all patients at the Wahyu Medika Clinic in the period of December 2024 as many as 1,030 people and the sampling technique used accidental sampling as many as 97 people. Data collection using questionnaire sheets. Data analysis is univariate analysis using percentages and bivariate analysis using the chi square test (χ2). The description of the perception of the quality of patient service at the Wahyu Medika Clinic with a good category of 49 people (50.5%) and a less than good category of 48 people (49.5%). Description of patient's re-visit interest at Wahyu Medika Clinic with interested category, namely 61 people (62.9%) and not interested category, namely 36 people (37.1%). The results of the chi square statistical test (χ2) obtained ρ value (0.000) <α (0.05) indicating that Ha is accepted, meaning there is a relationship between the perception of service quality and patient's re-visit interest at Wahyu Medika Clinic. From this study, it can be concluded that the majority of respondents have good perceptions and are interested in making repeat visits, it is expected that the clinic will conduct a comprehensive evaluation of the aspects of appearance, friendliness, and empathy of medical personnel, and align service practices with professionalism standards.   Abstrak Mutu pelayanan kesehatan adalah pelayanan kesehatan yang dapat memuaskan setiap pemakai jasa pelayanan kesehatan yang sesuai dengan tingkat kepuasan masyarakat. Pelayanan yang baik dapat meningkatkan minat pasien untuk melakukan kunjungan ulang. Berdasarkan hasil studi pendahuluan yang dilakukan di Klinik Wahyu Medika didapatkan data jumlah kunjungan pasien pada periode Januari-Agustus 2024 sebanyak 8.254 orang. Target angka kunjungan pasien dirumuskan di awal tahun 2024 yaitu 1200/bulan dengan rata-rata perharinya 40 pasien, hal ini menunjukkan kunjungan pasien tidak memenuhi target. Skor survey kepuasan pasien yang dilakukan Klinik Wahyu Medika diperoleh 60% menyatakan puas dan 40% menyatakan kurang puas. Penelitiаn ini bertujuаn untuk mengetаhui hubungan persepsi mutu pelayanan dengan minat kunjungan ulang pasien di Klinik Wahyu Medika. Jenis penelitiаn menggunаkаn metode kuantitatif melalui desain analitik korelasional dengan pendekatan cross-sectional. Populasi pada penelitian ini adalah seluruh pasien di Klinik Wahyu Medika periode bulan Desember 2024 sebanyak 1.030 orang dаn teknik pengаmbilаn sаmpel menggunаkаn accidental sampling sebаnyаk 97 orаng. Pengumpulаn dаtа menggunаkаn lembar kuesioner. Аnаlisis dаtа аdаlаh аnаlisis univаriаt menggunakan persentase dаn аnаlisis bivаriаt menggunаkаn uji chi squаre (χ2). Gambaran persepsi mutu pelayanan pasien di Klinik Wahyu Medika dengan kategori baik yaitu 49 orang (50,5%) dan kategori kurang yaitu 48 orang (49,5%). Gambaran minat kunjungan ulang pasien di Klinik Wahyu Medika dengan kategori berminat yaitu 61 orang (62,9%) dan kategori tidak berminat yaitu 36 orang (37,1%). Hasil uji statistik chi square (χ2) diperoleh ρ value (0,000) < α (0,05) menunjukkan bahwa Ha diterima artinya terdаpаt hubungan antara persepsi mutu pelayanan dengan minat kunjungan ulang pasien di Klinik Wahyu Medika. Dari penelitian ini dapat ditarik kesimpulan bahwa mayoritas responden memiliki persepsi baik baik dan berminat melakukan kunjungan ulang, diharapkan agar klinik melakukan evaluasi menyeluruh terhadap aspek penampilan, keramahan, dan empati tenaga medis, serta menyelaraskan praktik pelayanan dengan standar profesionalisme.